Síntese de fotocatalisadores baseados em óxidos de ferro e dióxido de titânio para aplicação em fotodegradação de Basagran® - Braga, Cristian Sergio (2019)
Contamination by agrochemicals has been approached with some frequency in the last years, the number of works presenting contaminations by pesticides in several matrices is increasing. Basagran® is a post-emergent herbicide classified by the manufacturer as highly toxic, persistent and mobile in the environment, which can cause contamination at the site of use or be carried, contaminating the whole course while active. Knowing the problems that can be caused by the herbicide, the work sought to synthesize possible photocatalysts based on iron oxides and titanium dioxide and to test the functionality of these photocatalysts in the degradation of the active principle of the Basagran® agrotoxic in a photoreactor of UV radiation that simulates the solar spectrum. Iron oxides II, III (Fe3O4), iron oxide III (Fe2O3) and titanium dioxide (TiO2), the latter derived from the synthesis of titanium isopropoxide, were used for this purpose. Tests were performed with five possible photocatalysts, being these Fe2O3, Fe2O3-TiO2 treated at 360 °C, Fe3O4, Fe3O4-TiO2 and Fe3O4-TiO2 treated at 360 °C. The particle that presented the best efficiency was that of Fe2O3-TiO2 treated at 360 °C, which in 120 minutes took the concentration of the pesticide from 1.3x10-4 mol L-1 to 6.4x10-5 mol L-1 degrading the pesticide in 51 % with degradation kinetics of k = 0.0058 min-1 showing an efficient process. The research has demonstrated that at least one of the synthesized particles functions as a photocatalyst and further, the recovery of the photocatalyst at the end of the process is facilitated, since the decanting of the fast iron oxide and provides for its recovery.